Cerebrospinal fluid abnormalities in HIV-negative patients with secondary and early latent syphilis and serum VDRL ≥ 1:32 - Maciej Pastuszczak; Jacek Zeman; Andrzej K Jaworek; Anna Wojas-Pelc (Wolters Kluwer Medknow Publications, 2013)
Background : Syphilis is caused by a spirochete Treponema pallidum. Invasion of the central nervous system (CNS) by T. pallidum may appear early during the course of disease. The diagnosis of confirmed neurosyphilis is based on the reactive Venereal Disease Research Laboratory (VDRL) in cerebrospinal fluid (CSF). Recent studies indicated that serum RPR ≥ 1:32 are associated with higher risk of reactivity of CSF VDRL. Aims : The main aim of the current study was to assess cerebrospinal fluid serological and biochemical abnormalities in HIV negative subjects with secondary and early latent syphilis and serum VDRL ≥ 1:32. Materials and Methods : Clinical and laboratory data of 33 HIV-negative patients with secondary and early latent syphilis, with the serum VDRL titer ≥ 1:32, who underwent a lumbar puncture and were treated in Department of Dermatology at Jagiellonian University School of Medicine in Cracow, were collected. Results : Clinical examination revealed no symptoms of CNS involvement in all patients. 18% ( n = 6) of patients met the criteria of confirmed neurosyphilis (reactive CSF-VDRL). In 14 (42%) patients CSF WBC count ≥ 5/ul was found, and in 13 (39%) subjects there was elevated CSF protein concentration (≥ 45 mg/dL). 10 patients had CSF WBC count ≥ 5/ul and/or elevated CSF protein concentration (≥ 45 mg/dL) but CSF-VDRL was not reactive. Conclusions : Indications for CSF examination in HIV-negative patients with early syphilis are the subject of discussion. It seems that all patients with syphilis and with CSF abnormalities (reactive serological tests, elevated CSF WBC count, elevated protein concentration) should be treated according to protocols for neurosyphilis. But there is a need for identification of biomarkes in order to identify a group of patients with syphilis, in whom risk of such abnormalities is high.